2011
DOI: 10.1101/gr.126201.111
|View full text |Cite
|
Sign up to set email alerts
|

Promoter architecture of mouse olfactory receptor genes

Abstract: Odorous chemicals are detected by the mouse main olfactory epithelium (MOE) by about 1100 types of olfactory receptors (OR) expressed by olfactory sensory neurons (OSNs). Each mature OSN is thought to express only one allele of a single OR gene. Major impediments to understand the transcriptional control of OR gene expression are the lack of a proper characterization of OR transcription start sites (TSSs) and promoters, and of regulatory transcripts at OR loci. We have applied the nanoCAGE technology to profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
83
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(88 citation statements)
references
References 53 publications
(79 reference statements)
3
83
1
1
Order By: Relevance
“…It has been clearly demonstrated that OR gene promoters are necessary for OR gene expression (6,7); however, because these promoters show similar cisregulatory elements (8)(9)(10)(11)(12), it is not clear how monogenic OR gene expression is achieved. Previous studies have identified cis-acting enhancers located upstream of OR gene clusters (denominated H and P elements) which can select one single gene for expression (13)(14)(15).…”
mentioning
confidence: 99%
“…It has been clearly demonstrated that OR gene promoters are necessary for OR gene expression (6,7); however, because these promoters show similar cisregulatory elements (8)(9)(10)(11)(12), it is not clear how monogenic OR gene expression is achieved. Previous studies have identified cis-acting enhancers located upstream of OR gene clusters (denominated H and P elements) which can select one single gene for expression (13)(14)(15).…”
mentioning
confidence: 99%
“…OR promoter sequences are required for the expression of OR transgenes, and an OR promoter is sufficient to drive MOE-specific expression of a reporter transgene (Plessy et al 2012; Rothman et al 2005; Vassalli et al 2002, 2011). These findings suggest that OR promoters contain sequences that are sufficient to recapitulate OR activation.…”
Section: Chromatin-mediated Silencing Of Olfactory Receptor Genes Is mentioning
confidence: 99%
“…Analyses of OR promoters have identified shared regulatory sequences (Clowney et al 2011; Michaloski et al 2006; 2011; Plessy et al 2012; Young et al 2011). These studies have reliably identified O/E family motifs and homeodomain motifs in most OR promoter sequences (Figure 2).…”
Section: Chromatin-mediated Silencing Of Olfactory Receptor Genes Is mentioning
confidence: 99%
“…Numerous studies have assayed the structure of OR promoters and proximal regions to identify factors required for OR expression (Michaloski et al 2006, Clowney et al 2011, Plessy et al 2012). A high-throughput analysis of OR promoters revealed a number of striking features.…”
Section: The Main Olfactory Epithelium: Olfactory Receptorsmentioning
confidence: 99%
“…OR promoters are enriched for homeodomain sites as well as for O/E (Olf1/early B cell factor)-like sites (Michaloski et al 2006, Clowney et al 2011, Plessy et al 2012). Two homeodomain proteins, LHX2 and EMX2, regulate OR gene expression.…”
Section: The Main Olfactory Epithelium: Olfactory Receptorsmentioning
confidence: 99%